The detours of pancreatic ducts, internal pancreatic fistulas: a rare complication of chronic pancreatitis - Satchithanandha, Vysheki; Park, Jin-Soo; Sandroussi, Charbel (International Surgery Journal, 2024)
Internal pancreatic fistula occurs due to the disruption of the pancreatic duct, resulting in communication with it and another epithelial surface. A rare variant is the pancreaticopleural and pancreaticogastric fistula, typically associated with chronic necrotising pancreatitis, resulting from posterior disruption of the pancreatic duct. It is a complex disease with different aetiologies, varied clinical presentations and multiple management options. Unlike postoperative pancreatic fistula, internal pancreatic fistula lacks guidelines for classification and management. Once an internal fistula is suspected, further imaging work-up and biochemical analysis needs to be performed. Here, we present an unprecedented case of pancreaticopleural fistula on a background of chronic necrotising pancreatitis, and an asymptomatic pancreatico-gastric fistula. To our knowledge, no such case has been previously reported.